Neurocognitive Effects of Repetitive Transcranial Magnetic Stimulation in Adolescents with Major Depressive Disorder - Wall, Christopher A.; Croarkin, Paul; McClintock, Shawn; Murphy, Lauren L.; Bandel, Lorelei A.; Sim, Leslie A.; Sampson, Shirlene M. (Frontiers in Psychiatry, 2013)
Objectives: It is estimated that 30% to 40% of adolescents with major depressive disorder (MDD) do not receive full benefit from current antidepressant therapies. Repetitive transcranial magnetic stimulation (rTMS) is a novel therapy approved by the US FDA to treat adults with MDD. Research suggests rTMS is not associated with adverse neurocognitive effects in adult populations; however, there is no documentation of its neurocognitive effects in adolescents. This is a secondary post hoc analysis of neurocognitive outcome in adolescents who were treated with open label rTMS in two separate studies. Methods: Eighteen patients (mean age, 16.2 ± 1.1 years; 11 females, 7 males) with MDD who failed to adequately respond to at least 1 antidepressant agent were enrolled in the studies. Fourteen patients completed all 30 rTMS treatments (5 days/week, 120% of motor threshold, 10 Hz, 3,000 stimulations per session) applied to the left dorsolateral prefrontal cortex (L-DLPFC). Depression was rated using the Children’s Depression Rating Scale-Revised (CDRS-R). Neurocognitive evaluation was performed at baseline and after completion of 30 rTMS treatments with the Children’s Auditory Verbal Learning Test (CAVLT) and Delis-Kaplan Executive Function System (DKEFS) Trail Making Test. Results: Over the course of 30 rTMS treatments, adolescents showed a substantial decrease in depression severity and a statistically significant improvement in memory and delayed verbal recall. Other learning and memory indices and executive function remained intact. Neither participants nor their family members reported clinically meaningful changes in neurocognitive function. Conclusion: These preliminary findings suggest rTMS does not adversely impact neurocognitive functioning in adolescents and may provide subtle enhancement of verbal memory as measured by the CAVLT. Further controlled investigations are warranted to confirm and extend these findings.